2022
DOI: 10.1099/mgen.0.000794
|View full text |Cite
|
Sign up to set email alerts
|

Finding the right fit: evaluation of short-read and long-read sequencing approaches to maximize the utility of clinical microbiome data

Abstract: A long-standing challenge in human microbiome research is achieving the taxonomic and functional resolution needed to generate testable hypotheses about the gut microbiota’s impact on health and disease. With a growing number of live microbial interventions in clinical development, this challenge is renewed by a need to understand the pharmacokinetics and pharmacodynamics of therapeutic candidates. While short-read sequencing of the bacterial 16S rRNA gene has been the standard for microbiota profiling, recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…4300 bp in size) consisting of the 16S rRNA gene, ITS region and 23S rRNA gene [ 117 ]. Targeting the combined 16S-ITS-23S regions instead of individual rRNA locus-derived fragments as commonly done in short read metabarcoding, can provide information on 16S and 23S gene sequences from single reads allowing strain level resolution of microbial communities, and improve diversity, divergence and phylogenetic estimations [ 117 , 118 , 119 , 120 , 121 ]. Depending on the primers used, sequencing of the RRN operon also enables identification and classification of Archaea and Bacteria from the same libraries [ 122 ].…”
Section: Sequencing Methodsmentioning
confidence: 99%
“…4300 bp in size) consisting of the 16S rRNA gene, ITS region and 23S rRNA gene [ 117 ]. Targeting the combined 16S-ITS-23S regions instead of individual rRNA locus-derived fragments as commonly done in short read metabarcoding, can provide information on 16S and 23S gene sequences from single reads allowing strain level resolution of microbial communities, and improve diversity, divergence and phylogenetic estimations [ 117 , 118 , 119 , 120 , 121 ]. Depending on the primers used, sequencing of the RRN operon also enables identification and classification of Archaea and Bacteria from the same libraries [ 122 ].…”
Section: Sequencing Methodsmentioning
confidence: 99%
“…The current stage of algorithms and approaches for LR metagenomics is still limited compared to the large toolbox of SR technologies. While the methodology used here re ects the most appropriate tools and algorithms available at the time, we recommend that future studies pursue a critical assessment of newer approaches [12] when using LR techniques. The dataset presented here can also serve as a reference for testing and comparing algorithms and approaches for shotgun LR metagenomic sequencing.…”
Section: Other Considerations When Choosing Lr Technologiesmentioning
confidence: 99%
“…For instance, current PacBio Sequel II technology offers circular consensus sequencing (CCS), providing a low-error rate in high delity reads, although at a shorter read length than the traditional long-read technology [3]. Additionally, better genome statistics (low number of contigs and high N50 values) [5][6][7][8][9] or the combination of short-and long-reads for the recovery of high-quality MAGs [10,11] have already showcased the bene ts for the recovery of microbial genomes [12]. Nonetheless, whether a switch from SR to LR metagenomic approaches would introduce biases for capturing the genetic potential of microbial populations in terms of recovery of the MAGs is less known.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that long-read sequencing technologies improve the contiguity of metagenomic assemblies and enable the recovery of repeated regions compared with short-read alternatives ( 1 , 2 ). To assess long-read technologies and evaluate dedicated bioinformatics tools, we performed deep sequencing of a human fecal metagenome with the PacBio Sequel II system.…”
Section: Announcementmentioning
confidence: 99%